Implementing Artificial Intelligence to Enhance Academic Information Retrieval for Final Project Fulfillment: Case Study in Library and Information Science Diponegoro University Students - Yulianto, Budhi; Ganggi, Roro Isyawati Permata (Universitas Islam Negeri Sumatera Utara, 2025)
Artificial intelligence poses problems about the authenticity of information and the potential for plagiarism. Students of Library and Information Science, as prospective professionals, hold a significant responsibility in comprehending and employing AI judiciously. This study intends to thoroughly investigate the function of AI in fulfilling students' information needs for their final assignments. This study employed a qualitative research method, utilizing a descriptive case study methodology alongside semi-structured interviews, observations, and document analysis. Researchers employed the Miles et al. analytical framework, which encompasses data reduction, presentation, and conclusion formulation. The results of this study indicate that there are two roles, which include: the first role is that AI assists students in brainstorming and determining research topics and theories related to those topics, and the second role is to obtain references and previous research as material for consideration in conducting researchStudents primarily concern themselves with the potential inaccuracy of AI-generated information, which may result in plagiarism in their final work.